Peran Publik dalam Mendorong Kinerja Media Layanan Publik dalam Mewujudkan Watak Kepublikannya - Effendy, Rochmad; Yulistiowati, Irma Mufita; Wibowo, Aryo Prakoso (Unitri Press, 2020)
The publicness character of the Indonesia Republic Radio/RRI is both historical as well as legal necessity. RRI was born from the historical process as a struggle radio to seize and defend independence from colonialists. This true identity that is embodied in the spirit of public service ethos is getting stronger after the enactment of Government Regulation No. 11/2005 and 12/2005 concerning public service broadcasting and RRI public service broadcasting respectively. The duty of serving the needs and interests of the public must be the